Kontribusi Peradaban Islam pada Dunia - Ghajali Rahman (Jurnal Syntax Transformation, 2021)
This article discusses the contribution of Islamic civilization in various fields of science to the progress of the world from the time of the Prophet Muhammad (peace be upon him) until the collapse of the Abbasid caliphate in 1258 AD. The progress of Islam is based on the teachings of Islam itself which teaches about the importance of science and glory for lmu claimants so as to give rise to the spirit for Muslims to study and develop science be it religious science or general science. The progress of Islamic civilization was also supported by Islamic leaders at that time to advance science, so that science developed rapidly in various fields of discipline and provide benefits that can be felt to this day. It cannot be denied that the progress of science today has the contribution of a glorious Islamic civilization. Therefore, it is important to show a claim to the contribution of ancient Islamic civilization through the innovation of studies by Muslim scientists today that integrates the Qur'an and science and technology